Biophysical and environmental changes in livestock disturbed areas in a South-American desert woodland. Potential implications for natural or assisted re-vegetation - Biruk, Lucía Nadia; Fernandez, María Elena; Aranibar, Julieta Nelida; Giordano, Carla Valeria (Elsevier, 2025)
Livestock breeding is among the main productive activities in drylands, often reducing vegetation cover, impacting the surrounding environment and plant regeneration. However, the magnitude of the change in environmental variables in response to vegetation changes has rarely been assessed in arid ecosystems. Our objective was to quantify changes in vegetation cover and floristic composition, as well as the associated microclimatic and edaphic variables that can challenge the ecosystem's restorative capacity in the Monte desert woodland of Argentina. We surveyed sites at 600 (disturbed) and 2000 m (relatively undisturbed) from five rural livestock posts. We found that disturbed sites had lower vegetation cover, altered floristic composition and more stressful environmental conditions for plants. The widest difference was a 50 % decrease in soil NO3−-N concentration, coupled with a 30 % increase in solar radiation (mainly UV-B), a 4 °C increase in air temperature, and coarser soil texture. Potential constraints to plant regeneration would be therefore not only related to low water availability, but also to lower fertility, higher radiation and temperature. Decisions on species selection to restore these ecosystems must therefore consider plant traits related to nutrient use and uptake capacity, and resistance to photo-oxidative stress, in addition to drought resistance.